2021
DOI: 10.1080/13603116.2021.1968515
|View full text |Cite
|
Sign up to set email alerts
|

Should we stay or should we go? Parent experiences of moving or considering moving their autistic child between mainstream schools

Abstract: She has worked as a secondary teacher and is the parent of an autistic child. Her research focuses on exploring nonessential school moves for autistic students. This article is based upon her research master's thesis completed at Griffith University.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 36 publications
1
7
0
Order By: Relevance
“…In contrast to this, an important finding of this review is that parents’ decisions around moving schools were influenced by factors both external and internal to the family. The findings of this review are also consistent with a recent study on mainstream school mobility in autism (Mitchelson et al, 2021 ) in which decisions around moving were well considered and influenced by a range of personal and practical considerations, such as the impact of school‐based issues on the family's time, finances and well‐being, as well as the quality or availability of alternative schools. This highlights that even though those parents who elect to move schools for their child may have felt a negative push away from their school, this push is only one factor influencing parents’ decisions.…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…In contrast to this, an important finding of this review is that parents’ decisions around moving schools were influenced by factors both external and internal to the family. The findings of this review are also consistent with a recent study on mainstream school mobility in autism (Mitchelson et al, 2021 ) in which decisions around moving were well considered and influenced by a range of personal and practical considerations, such as the impact of school‐based issues on the family's time, finances and well‐being, as well as the quality or availability of alternative schools. This highlights that even though those parents who elect to move schools for their child may have felt a negative push away from their school, this push is only one factor influencing parents’ decisions.…”
Section: Discussionsupporting
confidence: 88%
“…The impact of the child's school experience on their mental health was a key factor leading to school mobility in all move types, except for mainstream to mainstream. There was little information on mainstream school mobility; however, previous research has shown that autistic students’ mainstream school experiences which lead to mobility, particularly around bullying from peers and staff, can affect their mental health (Brede et al, 2017 ; Mitchelson et al, 2021 ). Bullying was mentioned across all move types in this review, with parents’ concerns for their child's safety being a priority in their decision to leave their placement (e.g., Lilley, 2015 ; Simmons & Campbell, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations